Recurrence of Schizophrenia Patients Based on Family Support Factors and Compliance with Medication - Fitria, Anjar Resti; Nurdina, Nurdina (Open Access Health Scientific Journal, 2024)
Background: Relapses in schizophrenia sufferers still occur frequently, so sufferers have to undergo a re-treatment process. Relapse in schizophrenia has a major impact on sufferers, families and health services. Lack of family support and patient non-compliance in taking medication are the most common factors in relapse.Methods: The method used in this writing is a literature review study. The library sources used came from Pubmed, Searchgate, and Google Scholar which were published from 2015 to 2020, and manually selected articles that were relevant or in accordance with the research questions.Results: Family support and medication adherence influence the relapse of schizophrenia sufferers. Family support provided is in the form of informational support, assessment support, instrumental support and emotional support. Non-compliance with taking medication in schizophrenia sufferers is caused by limited costs, drug diversity, drug side effects, and family attitudes that are not open.Conclusion: the influence of family support factors on schizophrenia recurrence is very high because the higher the support provided by the family will increase coping and motivate sufferers to recover quickly from their illness. The influence of adherence to taking medication in schizophrenia sufferers is very high because sufferers who do not comply with taking medication are more at risk of experiencing a relapse compared to sufferers who adhere to taking medication. The most dominant factor influencing recurrence is compliance with taking medication